2019
DOI: 10.1016/j.cej.2018.12.149
|View full text |Cite
|
Sign up to set email alerts
|

SO2 promoted in situ recovery of thermally deactivated Fe2(SO4)3/TiO2 NH3-SCR catalysts: From experimental work to theoretical study

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…In the previous studies, Yu et al found that the dispersed Fe 2 (SO 4 ) 3 /TiO 2 could be decomposed at ∼400 °C (2Fe 2 (SO 4 ) 3 → 2Fe 2 O 3 + 6SO 2 + 3O 2 ) and recovered via sulfation process at 350 °C. 56 58 Based on these reports, it could be confirmed that the decomposed sulfates in stage C should be Fe 2 (SO 4 ) 3 species. Obviously, the weight loss increases with the rise of poisoning temperature, marking the sulfate formation at a larger amount.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the previous studies, Yu et al found that the dispersed Fe 2 (SO 4 ) 3 /TiO 2 could be decomposed at ∼400 °C (2Fe 2 (SO 4 ) 3 → 2Fe 2 O 3 + 6SO 2 + 3O 2 ) and recovered via sulfation process at 350 °C. 56 58 Based on these reports, it could be confirmed that the decomposed sulfates in stage C should be Fe 2 (SO 4 ) 3 species. Obviously, the weight loss increases with the rise of poisoning temperature, marking the sulfate formation at a larger amount.…”
Section: Resultsmentioning
confidence: 92%
“…After poisoning with SO 2 and O 2 , the first reduction peak of sulfated catalysts (Figure 4A) could be assigned to the reduction of FeVO 4 , α-Fe 2 O 3 , and formed Fe 2 (SO 4 ) 3 species, as Fe 2 (SO 4 ) 3 could be reduced at ∼500 °C (Figure S11) and release negligible SO 2 simultaneously (Fe 2 (SO 4 ) 3 + 6H 2 → 2Fe + 3SO 2 + 6H 2 O). 56 It should be pointed out that the released SO 2 could not be detected by TCD in the argon (Ar) flow due to the similar thermal conductivity of SO 2 and Ar (Figure S11), so the SO 2 could scarcely affect the H 2 -TPR results. Notably, the first reduction peak was gradually shifted to a higher temperature region, and the H 2 consumption ratios of P α also unremittingly increased with the rise of sulfation temperature, indicating the continuous decrease of the redox properties due to the content growth of the stable Fe 2 (SO 4 ) 3 species.…”
Section: H 2 -Tpr Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen oxides (NO x , standing for NO and NO 2 ) are among the most harmful air pollutants which can lead to the formation of acid rain, photochemical fumes, ozone depletion, and climate change. Governments and related institutions have paid considerable attention to reducing the emission of NO x from vehicle exhaust and electric power plants. , NH 3 selective catalytic reduction (NH 3 -SCR) of NO x has been considered as an advanced technology for the elimination of nitrogen oxides from coal-fired power plants owing to the low cost and high efficiency. , At present, in the field of fixed source denitrification, the V 2 O 5 /TiO 2 catalyst has attracted extensive interest due to its good selectivity, high catalytic activity at 260–450 °C, stable properties, anti-poisoning ability, and strong anti-aging performance. Despite these considerable advantages, there are still some problems including narrow window of operation temperature, biological toxicity, and increasing energy consumption, which have impeded the practical application of the V 2 O 5 –WO 3 (MoO 3 )/TiO 2 catalyst system. …”
Section: Introductionmentioning
confidence: 99%
“…57 As reduction reaction was performed, the characteristic peaks at 711.1 and 724.7 eV were attributed to Fe 2p 3/2 and Fe 2p 1/2 in ferric trioxide and those at 711.6 and 725.2 eV were attributed to Fe 2p 3/2 and Fe 2p 1/2 in ferric sulfate 58 due to air oxidation after reduction. When reduction time was 3 h, the peak of ferric oxide slightly shifted to 710.7 and 724.3 eV, and the peak at 713.7 and 727.3 eV appeared, corresponding to Fe 2p 3/2 and Fe 2p 1/2 in ferric sulfate, 59 which may be attributed to the adsorption of the particle surface. According to Figure 8d, there were two kinds of sulfur in the raw materials, among which the peaks at 168.4 and 169.6 eV were related to S 2p 3/2 and S 2p 1/2 in sulfate and those at 164.1 and 165.3 eV were attributed to S 2p 3/2 and S 2p 1/2 in divalent sulfur.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%